Do Credit Risk Management and the Break-Even Point (BEP) Affect Profitability and Operational Sustainability? Evidence from Rural Banks in Indonesia - Isnaen, Fauzi; Albatsiah, Fauzan Akbar (Manunggal Halim Jaya, 2026)
This study analyzes the relationship between credit risk management and Break Even Point (BEP) on the profitability and operational sustainability of PT BPR Artha Bersama, a rural bank in Indonesia registered under the Financial Services Authority (OJK). Using a qualitative descriptive approach with data collected through interviews, observation, and documentation from 2020 to 2024, the findings reveal that credit risk, measured by the Non-Performing Loan (NPL) ratio, remained within healthy to very healthy levels (0.36%–2.58%), while the Loan to Deposit Ratio (LDR) consistently stayed in the very healthy category (33.58%–64.21%). The BEP calculation showed positive net gains each year, indicating the bank consistently achieved profitability above the break-even point. When credit risk is low and well-managed, it does not significantly hinder BEP achievement or profitability. Conversely, high and uncontrolled credit risk would substantially raise the BEP and reduce profitability. The bank implements several strategies, including stricter credit analysis, periodic monitoring, staff training, and collaboration with guarantee institutions. The study is limited to a single bank over five years; future research should expand to multiple rural banks. For practical implications, management should strengthen early detection systems for problematic credit and optimize operational efficiency. From a social perspective, effective credit risk management supports local economic development and preserves public trust in micro and small enterprise financing. The originality lies in simultaneously analyzing credit risk and BEP within a single framework specific to the Indonesian rural banking context, offering empirical evidence that managed credit risk enables sustainable BEP achievement and operational continuity.